Why nations fail : the origins of power, prosperity and poverty - Acemoglu, Daron; Robinson, James A., 1960- (London : Profile, 2012)
Why are some nations rich and others poor? Is it culture, the weather, geography? Perhaps ignorance of the right policies? Simply, no. None of these factors is either definitive or destiny. Daron Acemoglu and James Robinson conclusively show that it is man-made political and economic institutions that underlie economic success (or lack of it). Based on fifteen years of original research, Acemoglu and Robinson marshall historical evidence from the Roman Empire to the Soviet Union, from Korea to Africa, to build a new theory of political economy with great relevance for the big questions of today, including: China has built an authoritarian growth machine. Will it continue to grow at such high speed and overwhelm the West? Is America moving from a virtuous circle, in which efforts by elites to aggrandize power are resisted, to a vicious one that enriches and empowers a small minority? What is the most effective way to help move billions of people from the rut of poverty to prosperity? This book will change the way you look at--and understand--the world.--From American publisher description.
Preface: Why Egyptians filled Tahrir Square to bring down Hosni Mubarak and what it means for our understanding of the causes of prosperity and poverty -- So close and yet so different : Nogales, Arizona, and Nogales, Sonora, have the same people, culture, and geography. Why is one rich and one poor? -- Theories that don't work : poor countries are poor not because of their geographies or cultures, or because their leaders do not know which policies will enrich their citizens -- The making of prosperity and poverty : how prosperity and poverty are determined by the incentives created by institutions, and how politics determines what institutions a nation has -- Small differences and critical junctures: the weight of history : how institutions change through political conflict and how the past shapes the present --'I've seen the future, and it works' : growth under extractive institutions : what Stalin, King Shyaam, the Neolithic Revolution, and the Maya city-states all had in common and how this explains why China's current economic growth cannot last -- Drifting apart : how institutions evolve over time, often slowly drifting apart -- The turning point : how a political revolution in 1688 changed institutions in England and led to the Industrial Revolution -- Not on our turf : barriers to development : why the politically powerful in many nations opposed the Industrial Revolution -- Reversing development : how European colonialism impoverished large parts of the world -- The diffusion of prosperity : how some parts of the world took different paths to prosperity from that of Britain -- The virtuous circle : how institutions that encourage prosperity create positive feedback loops that prevent the efforts by elites to undermine them -- The vicious circle : how institutions that create poverty generate negative feedback loops and endure -- Why nations fail today : institutions, institutions, institutions -- Breaking the mold : how a few countries changed their economic trajectory by changing their institutions -- Understanding prosperity and poverty : how the world could have been different and how understanding this can explain why most attempts to combat poverty have failed.
Bibliography : p. [483]-509. - Includes index.
Koleksi Sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Institutional economics; Economic anthropology; Economic history -- 1945-; Failed states